The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/codi.15148
|View full text |Cite
|
Sign up to set email alerts
|

Could FiLaC™ be effective in the treatment of anal fistulas? A systematic review of observational studies and proportional meta‐analysis

Abstract: Aim Fistula Laser Closure (FiLaC TM) is a novel sphincter-preserving technique that is based on new technologies and shows promising results in repairing anal fistulas whilst maintaining external sphincter function. The aim of the present meta-analysis is to present the efficacy and the safety of FiLaC TM in the management of anal fistula disease. Method The present proportional meta-analysis was designed using the PRISMA and AMSTAR guidelines. We searched MEDLINE, Scopus, clinicaltrials.gov, Embase, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
12
0
4
Order By: Relevance
“…These two concurrently assisted the laser probe to attain primary closure. Common complications after FILAC was pain and discomfort, minor bleeding, fever, and late abscess [ 8 ]. Recovery is achieved within 6 months with no complication reported.…”
Section: Clinical Discussion and Conclusionmentioning
confidence: 99%
“…These two concurrently assisted the laser probe to attain primary closure. Common complications after FILAC was pain and discomfort, minor bleeding, fever, and late abscess [ 8 ]. Recovery is achieved within 6 months with no complication reported.…”
Section: Clinical Discussion and Conclusionmentioning
confidence: 99%
“…LAFT tedavisi ile anal fistülün iyileşme oranları değişiklikler göstermektedir. 476 hastayı içeren 8 çalışmanın meta-analizinde, fistül traktı Lazer Ablasyonu sonrasında ortalama iyileşme oranı % 63 ve postoperatif komplikasyon oranı %8 olarak bulunmuştur (22,23). Bununla birlikte, yayınlanmış serilerde başarı oranları, büyük yayılma için tek bir bariz neden olmaksızın % 20-%80 arasında önemli ölçüde değişiklik göstermektedir (6,24,25).…”
Section: Discussionunclassified
“…LIFT benzer başarı ve nüks oranlarına sahiptir ancak perinede ilave insizyon gerektirmektedir. VAAFT'den sonra ortalama başarı oranını %76.01 ve ortalama komplikasyon oranını %16.2 gösterdi (22). VAAFT benzer başarı oranına karşın komplikasyon oranı LAFT'a göre daha yüksek olduğu görülmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…LAFT is a method developed by Wilhelm A. to preserve the integrity and continuity of the sphincter and is based on laser probe ablation of the granulation tissue in the fistula canal (Wilhelm, 2011). It has been reported that the LAFT technique is successful in healing anal fistula at rates varying between 40% and 88% (Oztürk and Gülcü, 2014;Wilhelm et al, 2017;Terzi et al, 2018;Brabender et al, 2020;Donmez and Hatipoglu, 2017;Giamundo et al, 2014;Elfeki et al, 2020;Frountzas et al, 2020). There are even clinics that find the technique to be disappointing and abandon the practice (Stijns et al, 2019).…”
Section: Introductionmentioning
confidence: 99%